Real roots of nonlinear systems of equations through a metaheuristic algorithm (2011)
This article describes the use of a numeric strategy to perform a metaheuristic optimization for finding the real roots of a nonlinear equation system. A theorem that shows why it can be treated as an optimization problem is shown. Some two-, three-, and fiveequationsystems are used as examples of the strategy.